Donor cell‐derived acute promyelocytic leukemia after allogeneic hematopoietic stem cell transplantation. (3rd September 2018) - Bouvier, Anne; Ribourtout, Bénédicte; François, Sylvie; Orvain, Corentin; Paz, Damien Luque; Beucher, Annaëlle; Guérard, Alexandre; Guardiola, Philippe; Ugo, Valérie; Blanchet, Odile; Geneviève, Franck; Schmidt, Aline; et al.
Abstract: Donor cell leukemia (DCL) is an infrequent complication after allogeneic hematopoietic stem cell transplantation (HSCT). Its true incidence is difficult to assess, although improvements in chimerism studies contributed to a better diagnosis of DCL. We report two rare cases of donor cell‐derived acute promyelocytic leukemia (APL). To our knowledge, only two cases have been described in the literature. Here, we report one male and one female patients with acute myeloid leukemia (AML), who developed an APL in donor cells after HSCT. The latency between HSCT and DCL was 279 and 43 months, respectively. Fluorescent in situ hybridation and chimerism monitoring analysis proved the donor origin of APL. Surprisingly, donor lymphocyte infusion provided a hematological response during 19 months in the female patient. The mechanisms associated with pathogenesis of DCL are unclear and seem to be multifactorial. Increasing worldwide allogeneic hematopoietic stem cell transplantation activity and potentially the age of donor could explain the increasing incidence of DCL in the future. It is highlighted that long‐term follow up of recipients will allow to report all cases of DCL, to clarify the genetic landscape and factors which contribute to DCL, to understand the response to DLI.